A cause greater than self : the journey of Captain Michael J. Daly, World War II Medal of Honor recipient - Ochs, Stephen J. (Williams-Ford Texas A&M University military history series, 2012)
"A privileged, hell-raising youth who had greatly embarrassed his family--and especially his war-hero father--by being dismissed from West Point, Michael J. Daly would go on to display selfless courage and heroic leadership on the battlefields of Europe during World War II. Starting as an enlisted man and rising through the ranks to become a captain and company commander, Daly's devotion to his men and his determination to live up to the ideals taught to him by his father led him to extraordinary acts of bravery on behalf of others, resulting in three Silver Stars, a Bronze Star with "V" attachment for valor, two Purple Hearts, and finally, the Medal of Honor. Historian Stephen J. Ochs mined archives and special collections and conducted numerous personal interviews with Daly, his family and friends, and the men whom he commanded and with whom he served. The result is a carefully constructed, in-depth portrait of a warrior-hero who found his life's deepest purpose, both during and after the war, in selfless service to others. After a period of post-war drift, Daly finally escaped the "hero's cage" and found renewed purpose through family and service. He became a board member at St. Vincent's Hospital in Bridgeport, Connecticut, where he again assumed the role of defender and guardian by championing the cause of the indigent poor and the terminally ill, earning the sobriquet, "conscience of the hospital." A Cause Greater than Self: The Journey of Captain Michael J. Daly, World War II Medal of Honor Recipient is at once a unique, father-son wartime saga, a coming-of-age narrative, and the tale of a heroic man's struggle to forge a new and meaningful postwar life. Daly's story also highlights the crucial role played by platoon and company infantry officers in winning both major battles like those on D-Day and in lesser-known campaigns such as those of the Colmar Pocket and in south-central Germany, further reinforcing the debt that Americans owe to them--especially those whose selfless courage merited the Medal of Honor."--Project Muse.